PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENINGKATAN PENGETAHUAN DAN PENURUNAN KEPADATAN TIKUS DI SUMURBOTO, KECAMATAN BANYUMANIK, SEMARANG - Martini Martini; Sri Yuliawati; Retno Hestiningsih; Nissa Kusariana; Sudjut Haryanto (Balai Besar Penelitian dan Pengembangan Vektor dan Reservoir Penyakit (B2P2VRP) Salatiga, 2019)
Semarang, the capital city of Central Java Province, is one of the endemic areas in Indonesia with increasing case fatality rate in the last three years. Accordingly, the educational intervention is fundamentally requested. The aim of the study was to evaluate the influence of health education intervention on the community knowledge improvement and its implication for reducing the rat populations. The study was performed using field experiment with pretest and post test designs. A total of 55 cadres and housewives joining on the various education program at Sumurboto Village, Banyumanik Sub district, Semarang was used as research subjects. The health education interventions introduced in the study were counselling and mentoring. ,Data were analyzed using paired t-test. The results revealed that the knowledge of the subject research significantly increased and the rat populations significantly decreased after being given the educational intervention. The rat species identified in Sumurboto Village were Rattus norvegicus, R. tanezumi, R. exulans and Suncus murinus. The knowledge score before and after the intervention was 80.87 and 88.83 respectively. Meanwhile, the rat populations measured by trap success method reduced from 8% to 6% after the intervention. Nevertheless, the rat population in Sumurboto Village is considerably relative high indicating that the village possessed a high risk on leptospirosis attack. It is strongly suggested that the health education intervention in the community should be regularly maintained in order to accelerate the knowledge of leptospirosis and reduce the rat populations.